1993
DOI: 10.1038/361371a0
|View full text |Cite
|
Sign up to set email alerts
|

A new photoreactivating enzyme that specifically repairs ultraviolet light-induced (6-4)photoproducts

Abstract: Cyclobutane pyrimidine dimers (CPDs) and pyrimidine (6-4) pyrimidone photoproducts ((6-4)photoproducts) are the two major classes of cytotoxic, mutagenic and carcinogenic DNA photoproducts produced by ultraviolet light irradiation of cells. The phenomenon of photoreactivation, the reduction of the lethal and mutagenic effects of ultraviolet radiation by simultaneous or subsequent irradiation with near ultraviolet or visible light, has been identified in several organisms and in some cases the enzymes that cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
197
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 284 publications
(202 citation statements)
references
References 19 publications
3
197
1
1
Order By: Relevance
“…It should also be noted that the DNA repair capacity of Drosophila cells is somewhat different from that of human cells. The most striking difference is that Drosophila cells have a 6 -4-photolyase, which specifically repairs (6 -4)PP in a light-dependent manner, but human cells lack this enzyme (45). The (6 -4)PP lesions are removed rapidly by nucleotide excision repair.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that the DNA repair capacity of Drosophila cells is somewhat different from that of human cells. The most striking difference is that Drosophila cells have a 6 -4-photolyase, which specifically repairs (6 -4)PP in a light-dependent manner, but human cells lack this enzyme (45). The (6 -4)PP lesions are removed rapidly by nucleotide excision repair.…”
Section: Discussionmentioning
confidence: 99%
“…CPD photolyase has 20 -30% sequence homology with (6 -4) photolyases and cryptochromes. The (6 -4) photolyase uses light to repair the (6 -4) photoproduct, which is another UV-induced DNA lesion (4,41). Cryptochromes control the light response in plants and animals (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant DNA technology considerably accelerated the pace of characterization of these enzymes (4 -7). However, it was only in 1993 that a photolyase that repairs the (6-4) photoproduct was also discovered (8). Similarly, in 1993, it was found that an Arabidopsis thaliana protein with high sequence homology to photolyase had no repair activity but functioned as a blue-light receptor (cryptochrome) for plant growth and development (9).…”
Section: Historical Perspectivementioning
confidence: 99%